2012
DOI: 10.1021/pr300084c
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Proteome ofMycoplasma genitalium

Abstract: Mycoplasma genitalium is a human pathogen associated with several sexually transmitted diseases. Proteomic technologies, along with other methods for global gene expression analysis, play a key role in understanding the mechanisms of bacterial pathogenesis and physiology. The proteome of M. genitalium, model of a minimal cell, has been extended using a combination of different proteomic approaches and technologies. The total proteome of this microorganism has been analyzed using gel-based and gel-free approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 60 publications
2
18
0
Order By: Relevance
“…Interestingly, our study validates the findings of a previous study which identified pyruvate dehydrogenase E1 α chain and the protein encoded by MG_328 as phosphoproteins of M. genitalium [47]. Recently, both these proteins were found on the surface of M. genitalium [48], thus suggesting the possibility that they can play a role in M. genitalium -host interaction. What is intriguing in this study, however, is the reduced phosphorylation of a protein (PDH) in a phosphatase (MG208) deficient mutant of M. genitalium .…”
Section: Resultssupporting
confidence: 90%
“…Interestingly, our study validates the findings of a previous study which identified pyruvate dehydrogenase E1 α chain and the protein encoded by MG_328 as phosphoproteins of M. genitalium [47]. Recently, both these proteins were found on the surface of M. genitalium [48], thus suggesting the possibility that they can play a role in M. genitalium -host interaction. What is intriguing in this study, however, is the reduced phosphorylation of a protein (PDH) in a phosphatase (MG208) deficient mutant of M. genitalium .…”
Section: Resultssupporting
confidence: 90%
“…In this study, a total of 404 of the 795 M. suis KI_3806 proteins corresponding to 50.8% of all encoded proteins were identified (Supporting Information Files 3 and 4). This identification ratio is in accordance with GeLC‐MS/MS protein identification levels for other cultivable mycoplasmas . The proteins were distributed as follows: 316 proteins in the M. suis enriched fraction (method A), 229 in the buffer‐soluble fraction (method B), and 268 proteins in the buffer‐insoluble fraction (method C).…”
supporting
confidence: 80%
“…M. bovis MAPs were fractionated using TX-114 as previously described [48] with minor modifications. In brief, M. bovis HB0801 pellet was re-suspended in PBS containing 4% TX-114 (Sigma) and 1 mM PMSF (Sigma) and kept for 3-5h at 4°C after scraping.…”
Section: Methodsmentioning
confidence: 99%